2006
DOI: 10.1007/s11155-006-9004-7
|View full text |Cite
|
Sign up to set email alerts
|

Computational Experience with Rigorous Error Bounds for the Netlib Linear Programming Library

Abstract: Abstract. The Netlib library of linear programming problems is a well known suite containing many real world applications. Recently it was shown by Ordóñez and Freund that 71% of these problems are ill-conditioned. Hence, numerical difficulties may occur. Here, we present rigorous results for this library that are computed by a verification method using interval arithmetic. In addition to the original input data of these problems we also consider interval input data. The computed rigorous bounds and the perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…In particular, for certain nonsmooth problems and ill-conditioned or ill-posed problems, the algorithm may quit when UF * − LF * < and the box containing the point x at which f (x) = UF * may be printed; the other boxes need not be further resolved or verified. Christian Keil and Christian Jansson [108] have been successful at handling a variety of difficult test problems from the Netlib LP test set 44 with this criterion. Basically, this process first uses an efficient commercial or open-source solver to compute an approximate solution with floating point arithmetic.…”
Section: Pitfalls and Clarificationsmentioning
confidence: 99%
“…In particular, for certain nonsmooth problems and ill-conditioned or ill-posed problems, the algorithm may quit when UF * − LF * < and the box containing the point x at which f (x) = UF * may be printed; the other boxes need not be further resolved or verified. Christian Keil and Christian Jansson [108] have been successful at handling a variety of difficult test problems from the Netlib LP test set 44 with this criterion. Basically, this process first uses an efficient commercial or open-source solver to compute an approximate solution with floating point arithmetic.…”
Section: Pitfalls and Clarificationsmentioning
confidence: 99%
“…Here we present a summary of our numerical results for the NETLIB suite of linear programming problems [33]. For details refer to [23]. The NETLIB collection contains problems with up to 15695 variables and 16675 constraints.…”
Section: Certificate Of Infeasibility In Branch and Bound Algorithmsmentioning
confidence: 99%
“…These problems are illposed in the sense of Hadamard; we used the measure in [38] and found that 71% of the problems have infinite condition number. (See also [29].) In particular, small changes in the data can result in large changes in the optimum x, y, z, see e.g.…”
Section: Netlib Set-ill-conditioned Problemsmentioning
confidence: 99%